2014
DOI: 10.3389/fnhum.2014.00131
|View full text |Cite
|
Sign up to set email alerts
|

Self-generated thoughts and depression: from daydreaming to depressive symptoms

Abstract: Human minds often engage in thoughts and feelings that are self-generated rather than stimulus-dependent, such as daydreaming. Recent research suggests that under certain circumstances, daydreaming is associated with adverse effects on cognition and affect. Based on recent literature about the influence of resting mind in relation to rumination and depression, this questionnaire study investigated mechanisms linking daydreaming to depressive symptoms. Specifically, an indirect effect model was tested in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 76 publications
(124 reference statements)
1
45
0
Order By: Relevance
“…In that sense, rumination is a specific subtype of spontaneous thought characterized by dominant negative thought content that is processed in an abstract and repetitive way so as to lock the train of thoughts into a thematically narrow content channel (Klinger, 2013;Watkins, 2008). Here it is important to note that this differs from many other instances in which spontaneous thought unfolds in an open, expansive, and divergent way (Marchetti et al, 2014;Watkins, 2010). …”
Section: Response Styles and Control Theories Of Ruminationmentioning
confidence: 98%
See 1 more Smart Citation
“…In that sense, rumination is a specific subtype of spontaneous thought characterized by dominant negative thought content that is processed in an abstract and repetitive way so as to lock the train of thoughts into a thematically narrow content channel (Klinger, 2013;Watkins, 2008). Here it is important to note that this differs from many other instances in which spontaneous thought unfolds in an open, expansive, and divergent way (Marchetti et al, 2014;Watkins, 2010). …”
Section: Response Styles and Control Theories Of Ruminationmentioning
confidence: 98%
“…Given the relevance of goals and mental habits in spontaneous thoughts, one might suspect a rather large overlap between ruminative thinking and daydreaming. However, correlational studies clearly report only moderate correlations Marchetti, Van de Putte, & Koster, 2014). One explanation for this is that the term daydreaming is often used to refer specifically to fanciful mental streams, whereas rumination is generally serious and uncreative.…”
Section: Response Styles and Control Theories Of Ruminationmentioning
confidence: 99%
“…For example, there is evidence to suggest that daydreaming may be detrimental to well-being due to its associations with dysphoria (Smallwood, O'Connor, Sudbery, & Obonsawin, 2007), depression (Carriere, Cheyne, & Smilek, 2008;Giambra & Traynor, 1978), rumination and self-focused attention (Marchetti, Van de Putte, & Koster, 2014) and feeling less happy in daily life (Killingsworth & Gilbert, 2010). However, research increasingly acknowledges that daydreaming is unlikely to be a homogenous experience and has begun to explore the conditions under which daydreaming is associated with negative and positive emotion.…”
Section: Daydreaming and Emotionmentioning
confidence: 99%
“…For example, a large-scale study using the experience sampling method revealed that people tended to be unhappier in their daily lives when their minds were wandering compared to when they were not; a follow-up timelag analysis found that mind-wandering was an antecedent of negative mood (Killingsworth & Gilbert, 2010). Moreover, evidence from clinically depressed and dysphoric samples also found a high frequency of mind-wandering was associated with depressed symptoms (Marchetti et al, 2014;Smallwood et al, 2007). However, another experimental study induced the positive and negative emotions in the laboratory and found negative emotions resulted in a higher frequency of mindwandering relative to positive emotions (Smallwood, Fitzgerald, Miles, Personality andIndividual Differences 92 (2016) 118-122 &Phillips, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Self-esteem, a global feeling of self-value or adequacy as a person (Rosenberg, 1965), might act as an important role in this relationship. One of the defining features of mindwandering is intrinsic spontaneous cognition (Smallwood & Schooler, 2015), which has been associated with increased attention on one's inner thoughts, emotions, and experience (Marchetti et al, 2012(Marchetti et al, , 2014. Increased mind-wandering may lead to the excessive self-attention (Mor & Winquist, 2002), which may increase the risk of self-evaluation and can be related to negative emotion.…”
Section: Introductionmentioning
confidence: 99%